Clinical Results of Localized Alveolar Ridge Augmentation with Bone Grafts Harvested from Symphysis in Comparison with Ramus - Reza Pourabbas; Saeed Nezafati (Tabriz University of Medical Sciences, 2007)
Background and aims. Autogenous onlay bone grafting is a common procedure for alveolar ridge augmentation. It has been suggested that the amount of healed bone after this technique would be significantly less than the initial quantity. The aim of this study was to determine the relationship between the various parameters influencing the outcome of ridge augmentation procedures. Materials and methods. Thirty-two patients, 17 males and 15 females (mean age 40 ± 8.66), requiring lateral ridge augmentation in the anterior maxilla were recruited. Bone grafts obtained from either the mandibular ramus or symphysis were grafted on the recipient site and the buccolingual dimensions of the edentulous ridge before and six months after the procedure were measured and the difference between them was considered as ridge augmentation (RA). Parameters including graft thickness (GT), graft area (GA) and donor site (DS) were also recorded. Results. Onlay bone grafts, taken from mandibular and symphysis areas, significantly increased the buccolingual dimension of the alveolar ridge (mean 1.98 ± 1.22 mm, p < 0.001). However, the mean RA by symphysis grafts was significantly greater than ramus grafts (2.49 mm vs. 1.48 mm). There was also a significant correlation between graft thickness, surface area and the amount of bone augmentation. Conclusion. Symphysis area provides thicker and larger grafts, which may result in a better clinical outcome in alveolar ridge augmentation.